"Safer at home": The effect of the COVID-19 lockdown on epidemiology, resource utilization, and outcomes at a large urban trauma center. Issue 4 (18th April 2021) - Chiba, Hiroto; Lewis, Meghan; Benjamin, Elizabeth R.; Jakob, Dominik A.; Liasidis, Panayiotis; Wong, Monica D.; Navarrete, Sixta; Carreon, Robert; Demetriades, Demetrios
Abstract : BACKGROUND: The COVID-19 pandemic has affected the entire global health care system. In California, because of a high burden of cases, a lockdown order was announced on March 19, 2020. This study investigated the impact of the lockdown on the epidemiology and outcomes of trauma admissions at the largest trauma center in Los Angeles. METHODS: A retrospective study comparing epidemiological and clinical characteristics and outcomes of trauma admissions during the lockdown period (March 20, 2020, to June 30, 2020) to a similar period in the previous year (March 20, 2019, to June 30, 2019) was performed. Data collection included demographics, mechanism of injury, prehospital transportation, substance use, injury severity, resource utilization, and outcomes. FINDINGS: There were 1, 202 admissions during the lockdown period in 2020 and 1, 143 during the same calendar period in 2019. Following the lockdown, there was a reduction in the automobile versus pedestrian admissions by 42.5%, motorcycle injuries by 38.7%, and bicycle accidents by 28.4% but no significant effect on the number of motor vehicle accident admissions. There was an increase in ground level falls by 32.5%, especially in the elderly group. The absolute number of gunshot wounds increased by 6.2% and knife injuries by 39.3%. Suicides increased by 38.5%. Positive testing for substance use increased by 20.9%. During the lockdown, patients suffered less severe trauma, with Injury Severity Score of <9 ( p < 0.001), as well as less severe head ( p = 0.001) and severe chest trauma ( p < 0.001). Trauma deaths were reduced by 27.9%, and the crude overall mortality was significantly lower during the lockdown period (4.1% vs. 5.9%, p = 0.046). Intensive care unit admission rates, mechanical ventilation, and intensive care unit length of stay were all reduced. CONCLUSION: The COVID-19 lockdown in 2020 had a significant effect on the epidemiology, clinical characteristics, and critical care resource utilization of trauma admissions in a large academic trauma center. These findings may help in planning and optimization of hospital resources during the pandemic. LEVEL OF EVIDENCE: Epidemiological study, level III; Retrospective observational, level III.